PENGARUH DESAIN BLADE TERHADAP PENINGKATANKINERJA HIDRODINAMIKA PITCH BALING - BALING - Aurora Anna Ruby, (2022)
Propeller is the main component of ship propulsion, so many innovations have been made to get a propeller that works optimally. Starting from the type of blade to the propeller pitch that can be adjusted as desired. However, problems such as cavitation cannot be avoided. Therefore, this research analyzes 3 types of propeller blades namely B Series, Au Outline, and Kaplan to find the most optimal hydrodynamic performance. The research was conducted by varying the speed of 125 rpm, 150 rpm, and 175 rpm. The method used is CFD simulation method on Ansys software. The simulation results show that the rotation speed affects the pressure value on the propeller foil. The faster the rotation, the greater the pressure received by the propeller. The difference in design affects the percentage of the propeller area that experiences cavitation. Keyword: Blade, Ansys, cavitation